2017
DOI: 10.1016/j.janxdis.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinician use of exposure therapy in community mental health settings

Abstract: Exposure therapy is recognized as the key component of cognitive-behavioral treatment for anxiety. However, exposure is the least used evidence-based treatment in community mental health settings and is the most challenging technique for clinicians to adopt within the context of effectiveness and implementation trials. Little work has examined clinician and organizational characteristics that predict use of exposure, which is important for identifying implementation strategies that may increase its use. In a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
81
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 57 publications
3
81
1
Order By: Relevance
“…In both quantitative and qualitative reports of delivering multiple EBPs in a system‐driven implementation in children's mental health, community therapists reported making Augmenting adaptations to EBPs more frequently than making Reducing/Reordering adaptations (Barnett et al, 2018; Dyson, Chlebowski, & Brookman‐Frazee, 2019; Lau et al, 2017). These findings were encouraging, given concerns that therapists may remove core components of EBPs that they consider potentially distressing to clients, such as exposure for anxiety or evidence‐based strategies such as role‐plays (Becker‐Haimes, et al, 2017). Instead, in these studies, therapists were most often deploying fidelity‐consistent, Augmenting adaptations in attempts to boost client engagement, acceptability, and understanding of the practice.…”
Section: Introductionmentioning
confidence: 89%
“…In both quantitative and qualitative reports of delivering multiple EBPs in a system‐driven implementation in children's mental health, community therapists reported making Augmenting adaptations to EBPs more frequently than making Reducing/Reordering adaptations (Barnett et al, 2018; Dyson, Chlebowski, & Brookman‐Frazee, 2019; Lau et al, 2017). These findings were encouraging, given concerns that therapists may remove core components of EBPs that they consider potentially distressing to clients, such as exposure for anxiety or evidence‐based strategies such as role‐plays (Becker‐Haimes, et al, 2017). Instead, in these studies, therapists were most often deploying fidelity‐consistent, Augmenting adaptations in attempts to boost client engagement, acceptability, and understanding of the practice.…”
Section: Introductionmentioning
confidence: 89%
“…Exposure therapy (“exposure”) is the key ingredient in cognitive‐behavioral therapy (CBT) leading to improved outcomes for anxiety and related disorders (Abramowitz, 2013; Higa‐McMillan, Francis, Rith‐Najarian, & Chorpita, 2016). Less than 30% of clinicians in routine clinical settings regularly use exposure with their anxious clients (e.g., Becker, Zayfert, & Anderson, 2004; Becker‐Haimes, Okamura et al, 2017; Cook, Biyanova, Elhai, Schnurr, & Coyne, 2010). Prior efforts to increase CBT use for anxiety have demonstrated success in increasing the use of strategies such as cognitive restructuring and relaxation (e.g., Becker, Becker, & Ginsburg, 2012; Hoyer et al, 2017) but little progress has been made in increasing clinician exposure use (Chu et al, 2015; Thomassin, Marchette, & Weisz, 2019).…”
mentioning
confidence: 99%
“…Prior work has demonstrated that general organizational variables important for EBP implementation (e.g., proficient culture, implementation climate, and transformational leadership) are related to improved overall adherence to EBPs in community settings (e.g., Beidas et al, 2014; Cook et al, 2015; Farahnak, Ehrhart, Torres, & Aarons, 2019; Sayer et al, 2017; Williams, Glisson, Hemmelgarn, & Green, 2017). However, they are unrelated to clinician use of in vivo exposures (Becker‐Haimes, Okamura et al, 2017). Implementation scientists have argued that in addition to supportive leadership capacity for EBP, it is critical for organizations to develop innovation‐specific capacity for a given intervention (i.e., the human, technical, and fiscal conditions required for successful implementation of an intervention); this is thought to precede more traditionally studied organizational variables in mental health implementation such as implementation climate (Flaspohler et al, 2008; Scaccia et al, 2015; Wandersman et al, 2008).…”
mentioning
confidence: 99%
“…In light of the consistent finding that exposure-based treatment provides significant benefit for anxiety and OCD sufferers, the remedy for addressing contamination fear in the era of COVID may not be suspending the intervention, but instead more careful training of clinicians about the physical and litigation risks. Indeed, inflated litigation risk is a significant predictor of disuse of exposure treatment ( Becker-Haimes et al, 2017 ).…”
Section: Litigationmentioning
confidence: 99%